Kerancagean Dalam Penggunaan Kata dan Istilah - Amas Suryadi (Jurnal Sosioteknologi, 2006)
Indonesian people are generally less precise and creative in using the Indonesian Language. Most of them are satisfied when other interlocutors understand what they said. This belief cannot be tolerated in both scientific and technology-related communication. The point is that science and technology requires preciseness. Many instances of impreciseness in scientific and technology-related communication result in negative impacts. Besides their being imprecise, they are less creative in using both dictions and terminologies of science and technology. The following are the examples of both imprecise and less creative use of language. In Indonesian, the word air minum, which means drinkable water in English, is confused with air bersih; the equivalence for both the English words discovery and invention is penemuan in Indonesian. The equivalence for the English words instruments, appliance, tool, utensil, and device is alat in Indonesian. If we were creative enough, the equivalence of the later words could be found in Indonesian and vernacular languages, which are, in fact, highly abundant. Therefore, it is time that we held in high esteem of Indonesian as the language for national communication, science, and technology. Hence, we are obliged to develop our precise and creative attitude in using Indonesian language so that Indonesian as the language of science and technology can be achieved. In other words, it is about time that our society was discouraged to being imprecise and less creative in using Indonesian in their both written and spoken communication although the mastery of a foreign language is important.